IS ROUTINE VACCINATION AGAINST HEPATITIS A NEEDED IN CHILDREN? EVALUATION OF PROPHYLAXIS WITH VACCINES IN SEVERAL REGIONS OF RUSSIAN FEDERATION - I.V. Shakhgil’dyan; M.I. Mikhaylov; N.I. Ershova; P.A. Khukhlovich; V.A. Khasanova; I.N. Lytkina; N.I. Shulakova; V.V. Romanenko; A.I. Yurovskih; A.A. Yasinskiy (Вопросы современной педиатрии, 2010)
The article presents data on effectiveness of routine vaccination against hepatitis A in children. The results of program of specific prophylaxis of hepatitis A in several regions of Russian Federation are analyzed. Perspectives of implementation of obtained experience are discussed.Key words: children, hepatitis A, routine vaccination, regional vaccination calendars.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(6):123-126)